Fecal matter transplant from Ace2 overexpressing mice counteracts chronic hypoxia‐induced pulmonary hypertension. (10th January 2022) - Oliveira, Aline C.; Yang, Tao; Li, Jing; Sharma, Ravindra K.; Karas, Marianthi K.; Bryant, Andrew J.; de Kloet, Annette D.; Krause, Eric G.; Joe, Bina; Richards, Elaine M.; Raizada, Mohan K.
Abstract: Recent evidence suggests pulmonary hypertension (PH), a disease of the pulmonary vasculature actually has multiorgan pathophysiology and perhaps etiology. Herein, we demonstrated that fecal matter transplantation from angiotensin‐converting enzyme 2 overexpressing mice counteracted the effects of chronic hypoxia to prevent pulmonary hypertension, neuroinflammation, and gut dysbiosis in wild type recipients.